Imaging-Based 4D aortic pressure mapping in Marfan syndrome patients: a matched case-control study - Leidenberger, Tilman Albert Ulrich; Gordon, Yaron; Farag, Mina; Delles, Michael; Sanches, Augusto F.; Fink, Matthias A.; Kallenbach, Klaus; Kauczor, Hans-Ulrich; Rengier, Fabian (The annals of thoracic surgery, 2020)
Background - Marfan syndrome predisposes to aortic aneurysm, dissection, and rupture. We sought to investigate aortic 4-dimensional (4D) relative pressure maps derived from 4D flow cardiovascular magnetic resonance to identify disease characteristic alterations of the intraaortic pressure field in Marfan patients with aortic root dilation compared with age- and sex-matched healthy controls. - Methods - This prospective case-control study included 11 Marfan patients with aortic root dilation (31 ± 5 years, 5 female) and 11 age- and sex-matched healthy controls (31 ± 8 years, 5 female) undergoing 4D flow cardiovascular magnetic resonance of the thoracic aorta. 4D relative pressure maps were computed and compared between groups for 8 aortic regions. - Results - Aortic root diameters were significantly larger in patients compared with controls (43 vs 31 mm, P < .001), but not in the proximal descending aorta (23 vs 21 mm, P = .19). Regional pressure gradients over the cardiac cycle were significantly altered in Marfan patients with significantly higher minimum pressure gradients in the proximal ascending aorta (-44.3 vs -97.0 mm Hg/m, P < .001) and significantly lower maximum pressure gradients in the proximal descending aorta (55.1 vs 82.3 mm Hg/m, P < .01). The latter finding was associated with pathologic vortical flow patterns. Regional pressure gradient at mid systole significantly correlated with aortic diameter (proximal ascending aorta: r = 0.73, P < .001; proximal descending aorta: r = -0.59, P = .004). - Conclusions - Noninvasive 4D pressure mapping derived from 4D flow cardiovascular magnetic resonance revealed significant alterations of spatiotemporal pressure characteristics in the thoracic aorta of Marfan patients. These alterations were most pronounced in the proximal ascending aorta and the proximal descending aorta, corresponding to the regions where aortic dissections often originate in Marfan patients.